Aedes–Chikungunya Virus Interaction: Key Role of Vector Midguts Microbiota and Its Saliva in the Host Infection - Monteiro, Valter Vinícius Silva; Navegantes-Lima, Kely Campos; de Lemos, Alessandra Bittencourt; da Silva, Guilherme Liberato; de Souza Gomes, Rafaelli; Reis, Jordano Ferreira; Rodrigues Junior, Luiz Carlos; da Silva, Onilda Santos; Romão, Pedro Roosevelt Torres; Monteiro, Marta Chagas (Frontiers in Microbiology, 2019)
Aedes mosquitoes are important vectors for emerging diseases caused by arboviruses, such as chikungunya (CHIKV). These viruses’ main transmitting species are Aedes aegypti and Aedes albopictus, which are present in tropical and subtropical climatic regions all over the globe. Knowledge of vector characteristics is fundamentally important to the understanding of virus transmission. Only female mosquitoes are able to transmit CHIKV to the vertebrate host since they are hematophagous. In addition, mosquito microbiota is fundamentally important to virus infection in the mosquito. Microorganisms are able to modulate viral transmission in the mosquito, such as bacteria of the Wolbachia genus, which are capable of preventing viral infection, or protozoans of the Ascogregarina species, which are capable of facilitating virus transmission between mosquitoes and larvae. The competence of the mosquito is also important in the transmission of the virus to the vertebrate host, since their saliva has several substances with biological effects, such as immunomodulators and anticoagulants, which are able to modulate the host's response to the virus, interfering in its pathogenicity and virulence. Understanding the Aedes vector-chikungunya interaction is fundamentally important since it can enable the search for new methods of combating the virus’ transmission.